Development and Validation of Verbal Emotion Vignettes in Portuguese, English, and German - Wingenbach, Tanja S. H.; Morello, Leticia Y.; Hack, Ana L.; Boggio, Paulo S. (Frontiers in Psychology, 2019)
Everyday human social interaction involves sharing experiences verbally and these experiences often include emotional content. Providing this context generally leads to the experience of emotions in the conversation partner. However, most emotion elicitation stimulus sets are based on images or film-sequences providing visual and/or auditory emotion cues. To assimilate what occurs within social interactions, the current study aimed at creating and validating verbal emotion vignettes as stimulus set to elicit emotions (anger, disgust, fear, sadness, happiness, gratitude, guilt, and neutral). Participants had to mentally immerse themselves in 40 vignettes and state which emotion they experienced next to the intensity of this emotion. The vignettes were validated on a large sample of native Portuguese-speakers (N = 229), but also on native English-speaking (N = 59) and native German-speaking (N = 50) samples to maximise applicability of the vignettes. Hierarchical cluster analyses showed that the vignettes mapped clearly on their target emotion categories in all three languages. The final stimulus sets each include 4 vignettes per emotion category plus 1 additional vignette per emotion category which can be used for task familiarisation procedures within research. The high agreement rates on the experienced emotion in combination with the medium to large intensity ratings in all three languages suggest that the stimulus sets are suitable for application in emotion research (e.g. emotion recognition or emotion elicitation).